Outcome of Limping Radicular Pain Due to Lumber Disc Herniation Treated with Lateral Recess Decompression without Discectomy: A Longitudinal Study - Muzamil, Abdul Razaque Mari, Syed Aamir Shah, Fahmida Arab Mallah, Rayif Rashid Kanth, Asim Shahzad (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To assess the outcome of limping radicular pain due to lumber disc herniation treated with lateral recess compression without discectomy Study design: A longitudinal study Place and Duration: This study was conducted at People’s University of Medical and Health Sciences for Women Nawabshah Pakistan from January 2020 to January 2021. Methodology: A total of 65 patients were selected for standalone lateral access decompression with a tube shaped retractors. All patients selected were having limping radicular pain. Study investigated the disc consistency and the existence of sequestrated pieces. VAS and ODI scores methods were used to examine the condition. Age, gender, bodyweight, duration of illness, profession, usage of painkillers, preoperative VAS score, and Pain and disability Index version (ODI) score were all collected from the participants Results: The stand alone lateral access decompression was carried out from 60 patients out of 65. The 5 patients that were endured were in need of sequestrated disc removal. The average age was 53 years (40-68years), the ratio of male and female was 1.41:1.21, and the average follow-up period was 4 years (3.1–5.7 years). Pre-surgical and post-surgical scores as well as the ODI scores were observed. Overall, 93 percent of patients were improved by the surgery.